P94 LOWER RATE OF MAJOR BLEEDING IN HIGH–RISK PATIENTS UNDERGOING LEFT ATRIAL APPENDAGE OCCLUSION: A PROPENSITY MATCHED COMPARISON WITH DIRECT ORAL ANTICOAGULATION. (18th May 2022) - Magnocavallo, M; Della Rocca, D; Vetta, G; Lavalle, C; Mariani, M; Schiavone, M; Carola, G; Mohanty, S; Bassiouny, M; Forleo, G; Burkhardt, D; Al–Ahmad, A; et al.
Abstract: Background: Stroke prophylaxis in very high risk (CHA2DS2–VASc ≥ 5) patients with atrial fibrillation (AF) is one of the major challenges faced by physicians. Specifically, initiating direct oral anticoagulants (DOACs) in these patients poses a therapeutic conundrum due to the concomitant high risk of bleeding. Left atrial appendage occlusion (LAAO) might be a potential alternative for thromboembolic (TE) prevention; however, there are no studies comparing these two strategies in very high–risk patients. Objective: To evaluate the efficacy of LAAO versus DOACs in AF patients at very high TE risk. Methods: Data were extracted from two prospective databases including 1053 Watchman and 1328 DOAC patients. Watchman patients with a CHA2DS2–VASc ≥ 5 accounted for 26.3% (n = 277). In order to attenuate the imbalance in covariates, a 1:1 propensity score matching technique was used (co–variates: age, sex, CHA2DS2–VASc and HAS–BLED scores). This method resulted in 554 matched patients (277 patients per group; mean age: 79±7y; 57.4% F; CHA2DS2–VASc: 5.8±0.9). The primary endpoint was a composite of cardiovascular (CV) death, TE events (Stroke/TIA/peripheral embolism) and clinically significant bleeding. The annual TE and major bleeding risks were estimated based on the CHA2DS2–VASc score and compared with the annualized observed risk. Results: After a mean follow–up of 26±7 months, total events were 55 (9.4 event rates per 100 patient–years) in LAAO group vs. 78 (14.9 event rates per 100 patient–years) in DOAC group. DOACs had a significantly higher risk of the primary endpoint (hazard ratio [HR]: 1.30; 95% confidence interval [CI]: 1.08 to 1.56; p = 0.03). TE events (HR: 1.15; 95% CI: 0.84 to 1.57; p = 0.63) and CV death (HR: 1.13; 95% CI: 0.84 to 1.54; p = 0.63) did not differ between groups. Major bleeding events were significantly lower in LAAO patients (HR: 0.75; 95% CI: 0.51 to 0.82; p = 0.04). The unadjusted estimated risk of TE events was 12.3% with LAAO and 12.4% with DOACs. The annualized incidence of TE was 3.2% with LAAO and 4.1% with DOACs, which led to a risk reduction of 74% and 67%, respectively. Conclusion: In a large cohort of AF patients at very high TE risk (CHA2DS2–VASc ≥ 5), LAAO showed similar stroke prevention but a significantly lower risk of major bleeding than DOACs during a > 2year follow–up.